Characteristics of the moringa mother tree in the population of East Flores, East Nusa Tenggara - Setiadi, Adi; Hosang, Evert Yulianes (Kultivasi, 2023)
The moringa plant (Moringa oleifera Lam.) is a member of the Moringaceae family that grows in Indonesia. Moringa plants have many benefits, both as a source of food, medicine, and cosmetics. The development of moringa plants in Indonesia has not been carried out because it is still constrained by the absence of a mother tree and a source of moringa seed gardens. This study aims to identify morphological characters and production potential in two populations of moringa plants. The research was conducted in August 2021 in East Flores District, East Nusa Tenggara Province. The research was conducted by determining the selected mother tree (SMT), observing morphological characters, and seed production. Exploration of selected parent trees was carried out using a survey method on two moringa plant populations in Tiwatobi and Harubala villages. Observations of plant morphological characters were carried out on quantitative and qualitative characters. The production potential is carried out by estimating the production of moringa seeds in each population. The results showed that there were 19 SMTs in the first population and 29 SMTs in the second population. There are 27 morphological characters that have been observed, with the potential for seed production in each population of 314,554 seeds and 529,538 seeds per year.Keywords: moringa, morphology, mother tree, seed, population